Reading the Lines: A Fresh Look at the Hebrew Bible. By Pamela Tamarkin Reis. Pp. x + 227. Peabody, MA: Hendrickson Publishers, 2002. isbn 1 56563 696 1. £17.95 - Rooke, Deborah W. (The journal of theological studies, 2005)
This book is a collection of eleven essays that have all been previously published in a range of academic journals, and have been revised somewhat for their present context. Reis is not a professional biblical scholar but a serious enthusiast who works from the basis that the text is to be approached and interpreted as it stands, as a whole, and as the work of a single purposive author, without resorting to tools such as textual emendation or source criticism in order to account for apparent unevennesses or discrepancies in the text. From this perspective she offers readings of the creation narratives in Genesis 1–2; Cain's (missing) words to Abel in Gen.